Trends in Supply Chain Management in the Colombian Pharmaceutical Sector (2007)
The main hypothesis of this study is that Colombian companies in the pharmaceutical sector use at least the50% of processes in the third level of SCOR model. This hypothesis is supported in national regulation requirements for the sector, which emulate international standards. Economic and cultural environments allow a second hypothesis: companies apply less than 75%of best practices suggested by the SCOR model. Four sub-sectors were studied: veterinary, medicinal plants, medicines and vitamins. These sectors represent approximately 90% of the pharmaceutical sector, and their study represents a first approach in learning about trends in the complete sector.